Time-Transgressive Salinic and Acadian Orogenesis, Magmatism and Old Red Sandstone Sedimentation in Newfoundland - van Staal, Cees; McNicoll, Vicki; Rogers, Neil (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
We propose an intimate relationship between Silurian terrestrial red bed sedimentation (Old Red Sandstone), slab breakoff-related magmatism and deformation in the Newfoundland Appalachians. Red bed sedimentation started during the Early Silurian, and records the progressive rise of the Salinic mountains in the tectonic hinterland of the orogen. The red beds were mainly deposited in molasse-style foreland basins in front of an eastpropagating terminal Salinic deformation front. New U–Pb zircon dating of volcanic rocks interlayered with the Silurian red beds in key structural locations yielded ages ranging between 425 and 418 Ma, which, combined with the existing geochronological database, suggests that the sedimentary rocks are progressively younger from west to east and overstep the accreted Gondwana- derived terranes. We propose that deposition of the red beds is a good proxy for the time of cratonization of the accreted terranes. Eastward migration of the Salinic deformation front was accompanied by eastward-widening of a slab-breakoff-related asthenospheric window. The latter is interpreted to have formed due to a combination of progressive steepening of the down-going plate following entrance of the leading edge of the Gander margin and its eduction. Gander margin eduction (reversed subduction) is proposed to have been instigated by the trench migration of the Acadian coastal arc built upon the trailing edge of the Gander margin, which developed contemporaneously with the Salinic collision. The resultant thinning of the lithosphere beneath the Salinic orogen, built upon the leading edge of the Gander margin immediately prior to the onset of the Early Devonian Acadian orogeny, set the stage for generation of the widespread bloom of Acadian magmatism.